Predictors of neoplastic disease in children with isolated pituitary stalk thickening. Issue 10 (14th May 2013) - Robison, Nathan J.; Prabhu, Sanjay P.; Sun, Pengling; Chi, Susan N.; Kieran, Mark W.; Manley, Peter E.; Cohen, Laurie E.; Goumnerova, Liliana; Smith, Edward R.; Scott, R. Michael; London, Wendy B.; Ullrich, Nicole J.
Abstract Background The significance of pituitary stalk thickening (PST) on magnetic resonance imaging (MRI) is often unclear. We evaluated presenting symptoms, MRI findings, clinical course, and outcome predictors of patients with PST. Procedure We used a computerized search of the medical record from 1995 to 2008 to identify patients with PST without pituitary mass on MRI. Baseline and follow‐up MRIs were reviewed in a blinded fashion. Relevant clinical data were abstracted. Results 69 patients with reported PST and adequate imaging for review were identified; 42 met study criteria. Median age at first abnormal MRI was 13.6 years (range: 0.8–19.7); 43% were male. Median follow‐up was 3.4 years (range 0–12.8). Patients with diabetes insipidus (DI) were significantly more likely to have a neoplastic process than those without (P = 0.0008). Of 16 patients with DI, 8 (50%) had a neoplastic process, including germ cell tumor (n = 4), Langerhans cell histiocytosis (n = 3), and lymphoma (n = 1). Among patients with DI, 7 (44%) also developed anterior pituitary hormone dysfunction (APD), either at presentation or on pre‐biopsy follow‐up, including 6/8 patients with stalk neoplasm and only 1/8 patients with non‐neoplastic PST (P = 0.04). Twenty‐six patients presented without DI; none was found to have neoplasm of the stalk except one patient with craniopharyngioma. Progression of PST on follow‐up imaging was significantly associated with a subsequent neoplastic diagnosis (P = 0.04). Conclusion Patients with PST without DI are unlikely to have a neoplastic process. Among patients with DI, APD or progressive stalk increase over time are predictive of neoplasia. Pediatr Blood Cancer 2013;60:1630–1635. © 2013 Wiley Periodicals, Inc.